Ocurrence of Clubroot Caused by Plasmodiophora brassicae on Kohlrabi in Korea - MinA Song; InYoung Choi; JeongHeub Song; KuiJae Lee; HyeonDong Shin; Victor Galea (Research in Plant Disease, 2019)
From 2016 to 2018, approximately 15% of kohlrabi were observed displaying significant clubroot symptoms in farmer's fields in Jeju, Korea. The initial infection appeared as hypertrophy of root hairs, and as the disease progressed, galls formation occurred on the main roots, finally disease progress resulted in yellowing and wilting of leaves. Pathogenicity was proven by artificial inoculation of plants with resting spore suspension, fulfilling Koch's postulates. The resting spore is one-celled, spherical and subspherical, colorless, and 3-5 mm in diameter. On the basis of the morphological characteristics and phylogenetic analyses of internal transcribed spacer rDNA, the causal agent was identified as Plasmodiophora brassicae. To our knowledge, this is the first report on the occurrence of P. brassicae on kohlrabi in Korea.